Molecular characterization of Giardia duodenalis in dogs from Brazil - Paz e Silva, Flavio M. [UNESP]; Monobe, Marina M. [UNESP]; Lopes, Raimundo S. [UNESP]; Araujo, Joao P. [UNESP] (Springer, 2012)
The intestinal protozoan parasite Giardia duodenalis (syn. Giardia intestinalis and Giardia lamblia) is a widespread enteric pathogen in human and domestic animals. This organism is one of the most common parasites in domestic dogs in Brazil. In this study, we determined the occurrence and genetic characterization of G. duodenalis isolated from dogs from south-central São Paulo state, Brazil. A total of 300 fecal samples were collected. Fecal specimens were screened for the presence of G. duodenalis using microscopy (zinc sulfate solution flotation technique) and polymerase chain reaction (PCR) targeting the small subunit ribosomal (SSU-rDNA) and glutamate dehydrogenase (GDH) genes. Genetic characterization was performed using restriction fragment length polymorphisms (RFLP) and sequencing analysis of the GDH gene. In addition, selected samples were further characterized by RFLP and sequencing of the beta-giardin gene. The overall occurrence of G. duodenalis was 17.3% (52/300). The occurrence was higher in stray dogs (28%) than in household dogs (6.25%). of the 36 PCR-positive samples that were selected for genotyping, only dog-specific genotype C (20 isolates), D (11 isolates) and mixed C+D (five isolates) isolates were detected in the study. This study provides current information on the infection rates of G. duodenalis genotypes in canine populations and describes for the first time the presence of mixed infections within host-specific C and D genotypes in dogs in Brazil. These genotypes were widespread and commonly found in domestic dogs living in urban and suburban environments of the studied area and confirmed the endemic status of Giardia in this region.